An Analysis of Inventory Management at MJS Restaurant Jakarta - Putra, Anar Arsyid Wali Masâ??ud; Yudoko, Gatot (Journal of Business and Management, 2013)
The emergences of business competition in Jakarta, especially in hospitality sector, become stronger. It also perceived by MJS, which has been in hospitality sector for 5 years. Therefore, it encourages MJS to be able to prepare a fully develop management in order to survive and thrive in the business competition. One of MJSâ€™ efforts is trying to maximize the effectiveness and efficiency of the supply chain process, which the inventory management becomes its main pillar, in order to deliver the best quality at the right price. MJS inventory management divided into three processes, namely Planning, Executing, and Controlling. Planning is a process that determines the forecast of demand and order quantity. Executing consist a series activity of inventory, which are incoming inventory, inventory storage, and inventory come out. Whereas, controlling is a process to make sure the entire inventory is come in, stored, and come out as planned. MJS face some problems in the three phases. The use of qualitative method that dominate the planning process, become inappropriate as MJS commonly found large difference between MJSâ€™s forecast and the reality in terms of the demand forecast. Besides, the other problems, such as errors in inventory storage and lack of controlling activity against the suppliers, increase the amount of damaged inventory. The use of inappropriate calculation method for demand forecasting and order quantity, and also the lack of standard operation procedure (SOP) that led to inconsistency of staffâ€™s performance, summed up into the main problem that faced by MJS. Therefore, MJS is recommended to use two operation management tools in order to minimize the possibility of that operation problems occur in the future. The use of quantitative method to calculate the demand forecast using a moving average technique and the calculation of optimal order quantity using a computerized Material Requirement Planning system are recommended to solve the problems in planning process. While, the implementation of SOP is recommended to prevent the inconsistency of staffâ€™s performance.Â Keywords: Inventory Management, Forecasting, Supply Chain Management, Optimal Order Quantity, MRP, SOP, MJS, Restaurant.